A review on skin aging: mechanisms and therapeutic strategies - Parwati V. Naikar; Revati D. Sagare; Mallikarjun; Dattatreya; Pratiksha Akki (Creative Pharma Assent, 2026)
Background: Skin aging is a complex process driven by multiple factors. In addition to hereditary factors and cellular aging, exposure to sunlight, air pollution, and lifestyle factors are extrinsic factors that stress the skin. Skin aging involves multiple biological processes influenced by both internal factors (age, skin type, cellular aging) and external factors such as ultraviolet radiation, air pollution, and lifestyle. These cause various changes in appearance, function, and structure. Methodology: An extensive search of the published scientific literature on the mechanisms of skin aging and anti-aging treatments was conducted. Articles related to oxidative stress, inflammation, ECM degradation, melanogenesis, and signaling pathways, including MAPK, NF-κB, Nrf2, TGF-/Smad, and mTOR, were critically reviewed. Results and Discussion: The evidence indicates that skin aging is associated with the production of reactive oxygen species (ROS), DNA lesions, persistent inflammation, collagen lysis, and defective cellular regenerative processes. Current novel interventions, including antioxidants, senolytics, stem cell therapy, telomere-shifting, epigenetic-modifying approaches, and Mitochondrial therapy directed toward mitophagy, have shown noteworthy effects in reducing the progression of skin aging. Also, herbal topical preparations containing bioactive phytoconstituents have proven to be a safe and effective modality. Conclusion: Skin aging is a result of an intricate network of cross-interrelated intrinsic and extrinsic factors involving various molecular pathways. Novel, more effective, and safer therapeutic approaches and preparations of bioactive herbal formulations appear promising for treating skin aging.